Dissemination of VIM-2 producing Pseudomonas aeruginosa ST233 at tertiary care hospitals in Egypt - Zafer, Mai Mahmoud (BMC Infect Dis, 2015)
BACKGROUND: Pseudomonas aeruginosa is an important nosocomial pathogen, commonly causing infections in immunocompromised patients. The aim of this study was to examine the genetic relatedness of metallo-beta-lactamase (MBL) producing carbapenem resistant Pseudomonas aeruginosa clinical isolates collected from 2 tertiary hospitals in Cairo, Egypt using Multi Locus sequence typing (MLST). METHODS: Phenotypic and genotypic detection of metallo-beta-lactamase for forty eight non-duplicate carbapenem resistant P. aeruginosa isolates were carried out. DNA sequencing and MLST were done. RESULTS: The bla(VIM-2) gene was highly prevalent (28/33 strains, 85%) among 33 MBL-positive P.aeruginosa isolates. MLST revealed eleven distinct Sequence Types (STs). A unique ST233 clone producing VIM-2 was documented by MLST in P.aeruginosa strains isolated from Cairo university hospitals. The high prevalence of VIM-2 producers was not due to the spread of a single clone. CONCLUSIONS: The findings of the present study clearly demonstrate that clones of VIM-2 positive in our hospitals are different from those reported from European studies. Prevalence of VIM-2 producers of the same clone was detected from surgical specimens whereas oncology related specimens were showing diverse clones.